Testing the Motion of Lunar Retroreflectors. Issue 11 (22nd November 2021) - Williams, James G.; Boggs, Dale H.
Abstract: The Moon lacks recognizable plates moving with respect to each other, unlike the Earth. Analysis of Lunar Laser Ranging data does not find large Earth‐like (>1 cm/year) relative motions for the five lunar retroreflectors. The distances between reflectors show few mm/year rates that are not statistically significant. Despite this lack of individual significance, curiously, all of the well determined distances have negative rates. There is an extra non‐synchronous lunar rotation rate of 1.0 ± 0.4 mas/yr that is suspected to arise from unmodeled very long period effects of physical libration in longitude. Plain Language Summary: The crust of the Earth is made up of plates that move with respect to one another. The Moon lacks geological evidence for such plates. There are five laser retroreflectors on the Moon and the rates of change of the distances between them are no more than a few millimeters per year with uncertainties of similar size. There is evidence for a rotation of the retroreflectors in longitude of about 0.001 s of arc per year. This overall rotation is suspected to arise from a slight extra rotation of the Moon in space that might be due to a deficiency in the theory of orientation. Key Points: Lunar Laser Ranging finds no evidence for plate motion on the Moon There is evidence for an extra non‐synchronous lunar rotation rate of about 1 mas/year